2019
DOI: 10.1177/1369433219859410
|View full text |Cite
|
Sign up to set email alerts
|

Shaking table tests of a single-span freestanding rocking bridge for seismic resilience and isolation

Abstract: Rocking philosophy has advantages to maintain a preferable post-earthquake serviceability as an alternative of seismic resistant systems. This article presents an experimental study on the seismic behavior of a rocking bridge with freestanding columns capped with a freely supported deck. A 1/10 scaled, single-span double-column freestanding bridge was constructed and tested on a shaking table. The experimental results showed that the bridge model could undergo large rocking with enough stability under earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In recent years, many researchers have also studied the seismic performance of the rocking bridges through dynamic time history analyses (Stanton et al, 2014; Thonstad et al, 2016), which verified the feasibility of the system and its seismic advantages compared with the cast-in-place bridges. Han and his colleagues (Du et al, 2019; Jia, 2018; Zhou et al, 2019a) carried out the shaking table tests on the bridge structures with single-span and multi-span double-column rocking bent, respectively (as shown in Figure 5).
Figure 5.Shaking table test of rocking bridge structure: (a) structure construction, (b) drift ratio responses (Zhou et al, 2019a).
…”
Section: Rocking Bridge Structuresmentioning
confidence: 99%
“…In recent years, many researchers have also studied the seismic performance of the rocking bridges through dynamic time history analyses (Stanton et al, 2014; Thonstad et al, 2016), which verified the feasibility of the system and its seismic advantages compared with the cast-in-place bridges. Han and his colleagues (Du et al, 2019; Jia, 2018; Zhou et al, 2019a) carried out the shaking table tests on the bridge structures with single-span and multi-span double-column rocking bent, respectively (as shown in Figure 5).
Figure 5.Shaking table test of rocking bridge structure: (a) structure construction, (b) drift ratio responses (Zhou et al, 2019a).
…”
Section: Rocking Bridge Structuresmentioning
confidence: 99%
“…It was found that all the nonlinear behaviours were concentrated in the replaceable plastic hinges and the other components such as the cap beam, the column and the footing remained elastic. Du et al (2019) carried out shake table tests on a single span freestanding rocking bridge system (Fig. 9c).…”
Section: Bridge With Psc Piersmentioning
confidence: 99%
“…Examples of such systems are the out of plane motion of masonry structures, 12–21 the motion of unanchored equipment, 22–33 and the response of ancient Greco‐Roman and Chinese temples 34–38 . Moreover, allowing a structure to uplift and sustain rocking motion can be used as a seismic design method 39–64 and references therein], because the uplift works as a mechanical fuse and limits the design forces of both the superstructure and the foundation.…”
Section: Introductionmentioning
confidence: 99%